As narrativas dos mestres e a história da capoeira em Teresina/PI: do pé do berimbau aos espaços escolares - Silva, Robson Carlos da (2012)
Capoeira as a manifestation of Brazilian culture and social phenomenon that involves people from different social classes and groups created and developed by slaves and their descendants in Brazil is capable of adding significant educational value providing a different look at the cultural diversity of our people historically constituted a privileged means of resistance and survival strategy in the midst of complex urban societies in Brazil where after decades of persecution and almost to extinction has reinvented itself and assumes the status of national culture being accepted in school curricula and culminating with their registration IPHAN as Intangible Cultural Heritage Brazil. This research sought to understand how it happened the historical process of insertion of the capoeira in school spaces and contribute to future studies and subsequent adoption of new sources of research in the field of cultural history in Piauí and Brazil. It’s based on the following problem: How did the historical trajectory of capoeira and the process of schooling of this culture through the narratives of capoeira masters of Teresina-PI? The main objective of the study was Investigate how it happened the historical trajectory of capoeira and the schooling process of this culture from the oral testimonies of capoeira masters of Teresina-PI. The research is qualitative and was based on the historiographical field of Cultural History the main method was the use of narratives memories of capoeira masters in Piauí combined and crossed with several sources several traces and fragments such as texts from newspapers and periodicals images and documents official or unofficial in an attempt to revisit rebuild and give meaning to the past. The masters of capoeira the principal actors of this story identified as holders of knowledge about their history and their educational processes and pioneers in teaching and keeping alive the tradition of this art are Master Caramuru Master Tucano Master Zé Carlos and Master Chocolate selected by representation and authority acquired and recognized in the world of capoeira forged in the struggle of the dynamics of this development. The main experience was to realize the extreme difficulty it is to tell the stories of people without history of marginalized groups and treated as less important in the context of official history a problem that worsens when seeking a story that is told by the subjects themselves who lived and built such a story. This is the case of a history of capoeira in Piauí where officials sources seem not to exist there is no care in registering the story of a culture in which the subjects are ordinary people with no social significance from the standpoint of who represents and can officially say "of the" and "about" the other. The research points to the understanding that capoeira of Piauí was born spontaneously just for the fun and joy of practicing an art of beauty and unusual plasticity a fight that gave respect to its practitioners from a small focus, in early 1970 coming to school by the year 1979 the "invasion" literal to school spaces. The narratives of the masters of capoeiras how that its practice is important in the imaginary of the Teresina city by the vastness of knowledge that characterize it as an instrument of awareness and development of criticality with their songs gestures stories traditions poetry secrets mandingas and magic spells where body and spirit fuse and can never be conceived in separate